Evaluation of the middle course of the Oder River contamination - Wolska, Małgorzata; Urbańska-Kozłowska, Halina (Instal, 2023)
Studies of water quality changes in the Oder River in its middle course near the city of Wroclaw, mainly concerning the content of organic substances, were conducted between the years 2017-2022. Over the period of five years, no significant worsening of the Oder River water quality has been observed with respect to the total organic carbon content, however, an increase in the concentrations of specific organic contaminants from the PFAS group was observed. An intense seasonal algae growth was found in spring and late summer, and the number of algae has increased with time. Diatoms are the most abundant algae type. Water from the Oder River contains large amounts of biogens (nitrates and phosphates), which promote microorganism growth in water.
Keywords: Oder River; micropollutants; perfluoroalkyl acids; algae